Evaluation of Herbalife Nutritional Supplements in the Hepatic Function of Rats - Davi Feder, Marcelo Rodrigues Bacci, Janaina Aparecida Boide Santos, Marília Tavares Campos de Oliveira Gaboardi, Carolina Stangenhaus, Juliana Klein Lewi, Marina Akiko Rampazzo Del Valle Shiroma, Paulo Emanuel Barbosa dos Santos Junqueira, Giuliana Petri, Fernando Luiz Affonso Fonseca (Journal of Applied Pharmaceutical Science, 2013)
The intake of nutritional supplements among people who aim for weight loss has increased all over the world given the fact it is easily acquired without the need of a medical prescription. The goal of this study was to research the presence of toxicity due to the intake of Herbalife protein supplements and shakes in an animal model. Twenty-one male Wistar rats were divided in three groups: control, shake and protein. The shake and protein groups received 100 mg/kg/day of the supplement whereas the control group received 0.5 mg/kg/day of water. Supplementation regimen lasted two months and after this period laboratory exams and histological analysis were performed in order to evaluate hepatic lesions. The groups showed no differences in values of GGT, alkaline phosphatase, AST, ALT, cholesterol, HDL or triglycerides. All the toxicity reports related to Herbalife supplements are over longer periods of time of intake than the period established in this model. There are no reports on how the response of rats to this kind of supplementation works. The mechanism of hepatotoxicity in humans suggests an immune-mediated reaction. The presented model could not show the expected toxicity, it is reasonable to conclude that there is a direct relation between hepatic lesions in humans and the intake of Herbalife supplements.
Keywords: Herbalife, Acute Hepatitis, Nutritional Supplements, Hepatic toxicity, Nutritional toxicity.